The Resource-Based View and The Concept of Value: The Role of Emergence in Value Creation - Luján Salazar, Luis Armando (Mercados y Negocios, 2017)
This theoretical paper deals with the concept of value. It asserts that value is the only and necessary condition in the resource-based view (RBV). It also argues that no resource or strategy is valuable per se: it is related to a configuration of resources, routines, and embedded assets. For example, concerning the RBV attribute of imitation, we can ask to what extent a valuable resource is independent of the rest of resources, and by extension, to what extent a configuration of resources is rare by itself. This paper discusses the emergence of value and it is embeddedness in a configuration of resources. Revising the concept of value could challenge the other main conditions in the RBV: rarity and cost of imitation, impossibility to replace with strategic substitutes. If the relations of these attributes with the rest of the resources are taken into account, we might have a better understanding of how value emerges and how a firm’s resources and capabilities are related with the creation of value.